Humanitarian diplomacy practitioners and their craft - Minear, Larry 1936-; Smith, Hazel 1954- (United Nations University Press, 2007)
Humanitarian professionals are on the front lines of today's internal armed conflicts, negotiating access through physical and diplomatic roadblocks to reach imperiled civilians. They frequent the corridors of power, interceding with politicians and diplomats in countries wracked by violence, in capitals of donor governments that underwrite humanitarian work, and at the United Nations Security Council. They provide the media with authoritative and catalytic information about situations of humanitarian extremity. Humanitarian Diplomacy offers a compendium of humanitarian operations in settings as diverse as the Balkans, Nepal, Somalia, and East Timor, from the 1970s in Cambodia and 1980s in Lebanon to more recent engagements in Colombia and Iraq. These unique experiences and insights from the field are framed by context-setting essays on the theory and practice of humanitarian diplomacy. This volume provides a unique resource for practitioners, policy communities, and students of humanitarian action, as well as for the concerned public.